Extraction by the repulsion method of the fourth maxillary premolar (Triadan 108) in a standing Crioulo breed horse: Case report (Research, Society and Development, 2024)
The objective of this article is to describe the case of a 4-year-old castrated male Crioulo breed horse diagnosed with fractures in the right and left fourth maxillary premolars (Triadan 108 and 208), along with the dental repulsion technique used and its clinical progress. Clinical and radiographic examination of the oral cavity revealed lesions on the buccal aspect of the maxillary teeth and the lingual aspect of the mandibular teeth, due to excessively sharp enamel points (ESEP) on the premolars and molars, radiolucent areas in the tooth root, loss of anatomical conformation (dorsal displacement of the crown), and fracture with lateral displacement of the fragment in the Triadan 108 and 208 dental elements. The patient underwent extraction using the dental repulsion method of the Triadan 108 dental element, curettage of the alveolar bone, and partial protection of the space with gauze and an acrylic resin plug. Systemic therapy included broad-spectrum antibiotic therapy, anti-inflammatories, analgesics, topical wound dressings, and periodic plug changes. The patient was discharged after 44 days of hospitalization, with complete intraoral and surgical wound healing. The dental repulsion method may be an effective and safe option for extracting fractured maxillary premolars in horses. Some complications were observed during treatment, but a satisfactory result was achieved regarding healing and return to a normal diet.